The use of E-learning tools in education during the COVID-19 pandemic: Literature Review - Alharbi, Omran; Alshammari, Yousef; Alharthi, Saud; Alsheehri, Nada; AlMutairi, Awatif; Almaqrn, Riam K. (Advances in Social Sciences Research Journal, 2020)
This paper concentrates on the impact of the use of E-learning tools during the COVID-19 pandemic. In more detail, this study reviews the literature on the integration of e-learning strategies into universities or schools due to difficulties with face-to-face learning caused by the coronavirus. The results of the review indicate that E-learning applications have proven to be very useful for learners and educators since they allow them to continue with their learning and teaching. However, some issues have emerged from the use of technology in institutions such as technical issues and a lack of training. Some recommendations will be provided in this paper.